2015
DOI: 10.1177/1060826514561989
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity Priming

Abstract: Most research on the link between masculinity-related constructs and psychology well-being has been conducted using correlational rather than experimental research designs. To address this limitation, this study tested the effects of activating men's subjective masculinity experiences on state self-esteem by randomly assigning 183 men into either a masculinity priming condition or a control priming condition. Consistent with the social identity paradigm, participants who received masculinity priming reported h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…However, the present study was designed to first elicit general conceptions of gender (i.e., masculinity), asking first what it means to be a man. This question, similar to those asked by Hammond and Mattis (2005) and Hunter and Davis (1992, 1994), was designed to use priming to influence participants to think about masculinity-in-general (Wong et al, 2015), and thus guide the conversation toward considering masculinity as a gendered entity independent of race. It was followed by a series of specific questions, none of which mentioned race.…”
Section: Methodsmentioning
confidence: 99%
“…However, the present study was designed to first elicit general conceptions of gender (i.e., masculinity), asking first what it means to be a man. This question, similar to those asked by Hammond and Mattis (2005) and Hunter and Davis (1992, 1994), was designed to use priming to influence participants to think about masculinity-in-general (Wong et al, 2015), and thus guide the conversation toward considering masculinity as a gendered entity independent of race. It was followed by a series of specific questions, none of which mentioned race.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of heterosexual SEM-where a man is typically "performing" relative to a submissive and passive woman-one might expect genital-specific self-esteem to have an influence on men. Furthermore, previous research has reported a relationship between state self-esteem and masculinity in that the more "masculine" the traits men were primed to reflect upon in themselves, the greater their reported levels of state self-esteem (Wong et al, 2015). The popular media-including sexually explicit movies, magazines, and websites-frequently emphasize the connection between penis size and masculinity and reinforce the message that "bigger is better" (Lever et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, life events can affect state self-esteem in either a positive or negative manner. For example, a study conducted by Wong et al (2015) had male participants primed to reflect upon stereotypically masculine moments that had occurred previously in their lifetime. The primed group ultimately reported higher levels of state self-esteem specifically regarding their masculinity relative to an unprimed control group.…”
Section: Conceptualizing Self-esteemmentioning
confidence: 99%
“…Social psychological research offers many examples of experimental manipulations and interventions that heighten the salience of masculinities, including stereotype threats (H. J. Johnson et al, 2012) and primes (Wong et al, 2015). However, relatively little is known about methods of reducing the salience of masculinities.…”
Section: Reconstruction and Deconstruction: An Overviewmentioning
confidence: 99%